The Effect of Covid-19 On Elementary School Education In Mareje Village - Darsono, Mochammad Faizal; Husen, Wan Ridwan (AbdimasMu UMTAS, 2023)
Since the Covid-19 pandemic hit, many policies have been taken as an effort to prevent the spread of the corona virus, one of which is policy in the education sector. Teaching and learning activities for all school children of all levels are carried out from home through an online or online system. Many obstacles were encountered during learning from home, children's difficulties in following and understanding the subject matter conveyed by the teacher generally occurred because the learning methods used were felt to be inappropriate in their application. In general, children complain about giving subject matter by the teacher which tends to be successive and overlapping, making it burdensome for children to be able to understand the subject matter provided. This can result in a decrease in children's learning motivation and have an impact on their report card grades. There is a need for assistance with learning assistance for school children at home to help guide and teach school children if they experience learning difficulties at home, thus increasing learning motivation. Parents also play an important role in the education of their children. Parents should pay attention to the education of their children because the role of parents is very important in the educational process for them. So parents must be able to provide good examples and habits from childhood or childhood. This activity was carried out by representatives of Muhammadiyah students throughout Indonesia in Mareje Village, Sheet District, West Lombok Regency. The implementation method used in this activity is the lecture plus method and discussion. Even so, there are still deficiencies due to constraints, namely there are limited adaptation abilities and mastery of information technology by teachers and students, inadequate facilities and infrastructure, limited internet access. Solutions that can be done can be in the form of direct and indirect solutions. The direct solution is provided by the school, while the indirect solution is in the form of government policy through the Ministry of Education of the Republic of Indonesia.